Maintenance and manipulation of somatosensory information in ventrolateral prefrontal cortex - Spitzer, Bernhard (Hum Brain Mapp, 2013)
Neuroimaging studies of working memory (WM) suggest that prefrontal cortex may assist sustained maintenance, but also internal manipulation, of stimulus representations in lower‐level areas. A different line of research in the somatosensory domain indicates that neuronal activity in ventrolateral prefrontal cortex (VLPFC) may also represent specific memory contents in itself, however leaving open to what extent top‐down control on lower‐level areas is exerted, or how internal manipulation processes are implemented. We used functional imaging and connectivity analysis to study static maintenance and internal manipulation of tactile working memory contents after physically identical stimulation conditions, in human subjects. While both tasks recruited similar subareas in the inferior frontal gyrus (IFG) in VLPFC, static maintenance of the tactile information was additionally characterized by increased functional coupling between IFG and primary somatosensory cortex. Independently, during internal manipulation, a quantitative representation of the task‐relevant information was evident in IFG itself, even in the absence of physical stimulation. Together, these findings demonstrate the functional diversity of activity within VLPFC according to different working memory demands, and underline the role of IFG as a core region in sensory WM processing. Hum Brain Mapp 35:2412–2423, 2014. © 2013 Wiley Periodicals, Inc.